Temperature-dependent characteristics of AlGaN/GaN FinFETs with sidewall MOS channel - Im, Ki-Sik; Kang, Hee-Sung; Kim, Do-Kywn; Vodapally, Sindhuri; Park, YoHan; Lee, Jae-Hoon; Kim, Yong-Tae; Cristoloveanu, Sorin; Lee, Jung-Hee (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
AlGaN/GaN fin-shaped field-effect transistors (FinFETs) with variable fin width have been fabricated and characterized. Low-temperature measurements reveal distinct operation modes for wide FinFET, narrow FinFET and planar FET. The wide fin device exhibits broad transconductance (g(m)) that decreases sublinearly with increasing temperature due to the existence of the sidewall metal-oxide-semiconductor (MOS) channel. By comparison, the conventional planar AlGaN/GaN metal-insulator-semiconductor heterostructure FET (MISHFET) features relatively narrow g(m) curve and near-exponentially decay of g(m) with temperature. The effect of the sidewall channel becomes more prominent for the narrow fin device and leads to two distinct g(m) peaks. The first peak at negative gate voltage corresponds to the two-dimensional electron gas (2-DEG) channel, while the second peak at positive gate voltage is related to the sidewall MOS channel. Measurements also show that the electrons in 2-DEG channel experience polar-optical-phonon scattering unlike the electrons in the sidewall MOS channel which are mainly subject to Coulomb scattering. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: PERFORMANCE; GAN